Positive Education in the United Arab Emirates: Navigating Through and Beyond the Global Pandemic - Tavis D. Jules; Ashley M. Mayworm; Amy C. Nelson Christensenv (Gulf Education and Social Policy Review)
Drawing on data from the emirate of Ras Al Khaimah (RAK) in the UAE, this study looks at using Positive Education (PE) to build strengths, competencies, well-being, and toughness in educational communities, to combat learning loss before and during the pandemic. We were interested in understanding how educational leaders, teachers, and students perceive PE and its impact on student well-being, as well as how well-equipped they were to handle the effects of the pandemic after participating in PE. Using qualitative data from semi-structured in-person interviews, focus groups, classroom observations, and document analysis, this study argues that PE supported students in coping with stressors associated with the pandemic. We show three significant findings. First, we found that the pandemic impacted student well-being in numerous academic and nonacademic ways. Second, our results demonstrate that PE was helpful in supporting student resilience and well-being during the pandemic. Third, data show that because PE was rolled out just before the pandemic began, the pandemic curtailed its full implementation. We conclude by recommending a whole school approach to PE that includes family members since the pandemic revealed that when students are engaged in remote learning or otherwise not face-to-face at school, it is critical that parents/families can support youth who may be struggling. Finally, we note the need for school-based support, like PE, to engender student resiliency.